(Internet) Gaming Disorder in DSM-5 and ICD-11: A Case of the Glass Half Empty or Half Full: (Internet) Le trouble du jeu dans le DSM-5 et la CIM-11: Un cas de verre à moitié vide et à moitié plein. (May 2021) - Borges, Guilherme; Orozco, Ricardo; Benjet, Corina; Mart´ınez, Kalina I. Mart´ınez; Contreras, Eunice Vargas; P´erez, Ana Lucia Jim´enez; Cedr´es, Alvaro Julio Pel´aez; Uribe, Praxedis Cristina Hern´andez; Couder, Mar´ıa Anabell Covarrubias D´ıaz; Gutierrez-Garcia, Ra´ ul A.; Ch´avez, Guillermo E. Quevedo; Albor, Yesica; et al.
Background: Diagnostic and Statistical Manual of Mental Disorders ( DSM -5) included in 2013 Internet gaming disorder (IGD) as a condition for further study, and in 2018, the World Health Organization included gaming disorder (GD) as a mental disorder in the International Classification of Disease ( ICD -11). We aim to compare disorders of gaming in both diagnostic systems using a sample of young adults in Mexico. Methods: Self-administered survey to estimate the prevalence of DSM -5 IGD and ICD -11 GD in 5 Mexican universities; 7, 022 first-year students who participated in the University Project for Healthy Students, part of the World Health Organization World Mental Health International College Student Initiative. Cross-tabulation, logistic regression, and item response theory were used to inform on 12- month prevalence of DSM -5 IGD and ICD -11 GD, without and with impairment. Results: The 12-month prevalence of DSM -5 IGD was 5.2% (95% CI, 4.7 to 5.8), almost twice as high as the prevalence using the ICD -11 GD criteria (2.7%; 95% CI, 2.4 to 3.1), and while adding an impairment requirement diminishes both estimates, prevalence remains larger in DSM -5. We found that DSM -5 cases detected and undetected by ICD -11 criteria were similar in demographics, comorbid mental disorders, service use, and impairment variables with the exception that cases detected by ICD -11 had a larger number of symptoms and were more likely to have probable drug dependence than undetected DSM -5 cases. Conclusion: DSM -5 cases detected by ICD -11 are mostly similar to cases undetected by ICD -11. By using ICD -11 instead of DSM -5, we may be leaving (similarly) affected people underserved. It is unlikely that purely epidemiological studies can solve this discrepancy and clinical validity studies maybe needed.